ذبیحہ شرعی اور اہل کتاب کے ذبیحہ کا مسئلہ ایک تحقیقی مطالعہ: Islamic Slaughter and Ruling on the slaughter of the people of the Book. A research Study. - Muhammad, Wali; Saleem, Dr.Muhammad; Ali, Muhammad (Journal of Quranic and Social Studies, 2021)
The food of the People of the Book includes the animals slaughtered by them. The rule that 'our food is lawful to them and theirs lawful to us' signifies that there need be no barriers between us and the People of the Book regarding food. We may eat with them and them with us. If the People of the Book either do not observe those principles of cleanliness and purity which are considered obligatory by the Law or if their food includes prohibited items, then one should abstain from eating them. If, for instance, they either slaughter an animal without pronouncing the name of God or if they slaughter it in the name of anyone else but God it is not lawful for us to eat that animal. The same applies to those non-Muslims who are not People of the Book, except for one difference - that whereas the animals slaughtered by the People of the Book are lawful provided they have pronounced the name of God at the time of slaughtering them, we are not permitted to eat the animals killed by non-Muslims who are not People of the Book.